Genotyping of UGT1A1*80 as an Alternative to UGT1A1*28 Genotyping in Spain - Adrián Bravo-Gómez; Sara Salvador-Martín; Paula Zapata-Cobo; María Sanjurjo-Sáez; Luis Andrés López-Fernández (MDPI AG, 2022)
Background: The variant rs34983651 (UGT1A1*28) and its genotyping are used to prevent irinotecan-induced toxicity. Several variants are in close linkage disequilibrium. Our objective was to evaluate the potential correlation of genotyping UGT1A1*80 instead of UGT1A1*28 in different populations. Methods: We studied SNPs in linkage disequilibrium with UGT1A1*28 in several populations and selected rs887829 to develop an inexpensive and rapid genotyping method and compare it with the one we currently use for UGT1A1*28 genotyping. Samples from cancer patients (n = 701) already tested using PCR and electrophoresis prior to treatment with irinotecan for rs34983651 (UGT1A1*28) in a Spanish hospital were genotyped for rs887829 (UGT1A1*80) using real-time PCR with a TaqMan probe. Results: We observed a complete match for both genotypes, except in one sample. This method was 100% efficient in correctly genotyping *28/*28 patients, 99.68% efficient for *1/*28, and 100% efficient for *1/*1. Linkage disequilibrium between populations showed the Iberian population to be the most suitable for the clinical use of UGT1A1*80. This method is less expensive and the time to decision is shorter. Conclusion: Genotyping of rs887829 using the proposed method may be used to substitute genotyping of rs34983651 as a pharmacogenetics test in cancer patients prior to starting irinotecan-based treatments, mainly in the Iberian population. In addition, it is less expensive than other conventional methods and easy to implement, with a shorter time to decision than UGT1A1*28.